PERANCANGAN SISTEM PENGENDALI GENSET BERBASIS ANDROID - Kustanto, Kustanto; Yudanto, Bramasto Wiryawan; Saputro, Daniel Tunggono (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2025)
ABSTRACTIn the era of digital technology, generator engines that are commonly used as electric generator drives can be controlled automatically and safely. In the design of this generator control system, it is a combination of communication technology with microcontroller technology. The millennial community today is no stranger to operating a communication device in the form of an android. The development of this device is able to transmit data to electronic devices in microcontroller packaging. The combination of android and microcontroller can be used by the system to control the generator engine remotely or closely. The benefit of this collaboration between android and microcontroller is that the generator can be turned on remotely when PLN is off. The results of this research are in the form of a prototype design of a generator control system using android with Bluetooth media.Keywords: Design, control system, generator, android, bluetooth.Keywords: Design, control system, generator, android.